Correlation of Specific Mutations in Line Probe Assay (LPA) and Drug Susceptibility Test (DST) with respect to Fluoroquinolone Resistance in Drug Resistant Mycobacterium tuberculosis. (4th October 2017) - Agrawal, Umang; Savaj, Pratik; Davda, Kanishka; Rodrigues, Camilla; Soman, Rajeev
Abstract: Background: This study was done to investigate the utility of specific fluoroquinolone mutations in LPA in predicting the susceptibility in DST at WHO recommended Critical Concentrations of 0.5 and 2 µg/dL of moxifloxacin within a short time frame as provided by LPA. Methods: In a retrospective study performed at a tertiary care hospital of Mumbai, India from October 2015 to February 2017, consecutive samples demonstrating fluoroquinolone resistance by LPA were selected. The LPA kit used was Hain Lifescience Genotype MTBDRsl (Version 1). It detects the following mutations in gyrA gene: MUT1: Ala90Val, MUT2: Ser91Pro, MUT3A: Asp94Ala, MUT3B: Asp94Asn/Tyr, MUT3C: Asp94Gly, MUT3D: Asp94His. The causal mutation was noted. For 89 of these samples, DST had been requested and results with Critical Concentration of 0.5µg/dL and 2µg/dL for moxifloxacin were available Results: The 89 samples studied were as follows: Sputum ( n = 60), paravertebral soft tissue ( n = 2), bronchoalveolar fluid ( n = 2), cerebrospinal fluid ( n = 1), endotracheal tube secretion ( n = 1), pleural fluid ( n = 1) and site not recorded (22). 3 of these samples had double mutations. Results are as follows. Conclusion: This study showed a higher proportion of M. tuberculosis susceptibility at 2 µg/dL rather than at 0.5 µg/dL, to moxifloxacin for gyrA mutations Ala90Val (MUT1), Asp94Ala (MUT3A), Asp94Gly (MUT3C), Asp94His (MUT3D) but not for Ser91Pro (MUT2) and Asp94Asn/Tyr (MUT3B). However, the number of samples with Ser91Pro (MUT2) and Asp94Asn/Tyr (MUT3B) mutations was too small for meaningful conclusion. This susceptibility at a higher critical concentration of moxifloxacin may have clinical implications for use of high dose moxifloxacin. Since this information is available within a short time frame as provided by LPA, a more effective regimen could be devised 4 to 8 weeks earlier than after results of DST. This may result in faster sputum conversion and prevent amplification of resistance. Disclosures: All authors: No reported disclosures.